Mental Practice untuk Menurunkan Kecemasan: Sebuah Meta-Analisis - Prastika Prima Nugraheni; Ananta Yudiarso (Jurnal Studia Insania, 2021)
Mental Practice (Relaxation, Imagery, and Self Talk has an inconsistent impact on reducing anxiety in previous studies. This study aims to determine the level of effectiveness of Mental Practice interventions to reduce anxiety. In this case, a review was carried out to 17 journals related to Mental Practice (Relaxation, Imagery, and Self Talk) with a total number of 1054 participants; 521 people in the Experiment group, and 533 people in the Control group.  Data processing is based on the number of sample size (N), mean (M), and standard deviation (SD), and by using the Random Effect Model criteria, the result of Hedges g is 1.19. From the result, it can be concluded that Mental Practice has a great effect in reducing someone’s anxiety